Comprehensive Functional Assessment of Right‐Sided Heart Using Speckle Tracking Strain for Patients with Pulmonary Hypertension. Issue 7 (26th February 2016) - Fukuda, Yuko; Tanaka, Hidekazu; Ryo‐Koriyama, Keiko; Motoji, Yoshiki; Sano, Hiroyuki; Shimoura, Hiroyuki; Ooka, Junichi; Toki, Hiromi; Sawa, Takuma; Mochizuki, Yasuhide; Matsumoto, Kensuke; Emoto, Noriaki; et al.
Abstract : Background: Right ventricular (RV) systolic function is one of the most important determinants of outcome for pulmonary hypertension (PH) patients, but the factors influencing prognosis vary widely. Elevated right atrial (RA) pressure is reported to be one of these prognostic factors, but its functional importance has scarcely been assessed. Methods: Eighty‐two PH patients, all of whom underwent echocardiography and right heart catheterization, were recruited. RV function was assessed by two‐dimensional speckle tracking longitudinal strain from RV‐focused apical four‐chamber view and calculated by averaging the three regional peak strains from the RV free wall (RV‐free). RA function was determined as the sum of three peak strain values comprising reservoir, conduit, and contractile function (sum of RA strain). Results: Sum of RA strain correlated significantly with hemodynamic parameters such as mean right atrial pressure (r = −0.35, P = 0.002) and end‐diastolic RV pressure (r = −0.29, P = 0.008). Patients with sum of RA strain ≥30.2% experienced more favorable outcomes than those with sum of RA strain <30.2% (log‐rank P = 0.001). Furthermore, patients with impaired RV systolic function (RV‐free <20%) and RA function (sum of RA strain <30.2%) showed the worst outcome (P = 0.001). A sequential Cox model based on clinical variables ( χ 2 = 5.8) was improved by addition of RV‐free ( χ 2 = 8.7; P < 0.05) and further improved by addition of sum of RA strain ( χ 2 = 12.0; P < 0.01). Conclusion: Right atrial strain appears to be a valuable additive factor for predicting outcomes for PH patients, and comprehensive functional assessment of right‐sided heart using speckle tracking strain may have potential clinical implications for better management of PH patients.